Atlantoid Occipital Assimilation: Malformation, Compensation or Deformity. Is it a Part of The Basilar Invagination? Terminology Review - Alemán-Iñiguez, Juan Miguel; Astudillo Pacheco, Pedro David; de La Torre Freire, Juan Sebastián (Revista Argentina de Neurocirugía, 2024)
Background. Atlantoid assimilation can occur alone or in association with other malformations and deformities of the craniocervical junction. The terms have evolved with the advancement of radiology and surgical techniques. Objectives. Describe a case of Atlantoid assimilation and review the associated terminology. Case description. A 60-year-old patient with asymmetrical pyramidal symptoms after falling from his own height and low-energy kinetics presented with magnetic resonance imaging with atlantoid assimilation. Intervention. Management was conservative with intermittent cervical orthosis, completely reversing the clinical picture. Currently the patient is under periodic clinical observation without relapses. Conclusion. Atlantoid occipital assimilation is a congenital malformation that is often asymptomatic; it is part of an embryological compensation when it is associated with other malformations. Atlanto-axial instability produces a rapidly evolving acquired deformity. Applying the appropriate terminology allows the correct understanding of the pathology and individualization of each case.